Impact of Percutaneous Transluminal Renal Angioplasty on Autonomic Nervous System and Natriuresis in Hypertensive Patients With Renal Artery Stenosis - Yoshio Iwashima; Hiroshi Kusunoki; Akira Taniyama; Takeshi Horio; Shin‐ichiro Hayashi; Masatsugu Kishida; Tetsuya Fukuda; Fumiki Yoshihara; Toshihiko Ishimitsu; Yuhei Kawano (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2022)
Background We investigated the early postoperative effect of percutaneous transluminal renal angioplasty on ambulatory blood pressure (BP) and the circadian characteristics of natriuresis and autonomic nerve activity. Methods and Results A total of 64 patients with hypertension with hemodynamically significant renal artery stenosis (mean age, 60.0±21.0 years; 31.3% fibromuscular dysplasia) who underwent angioplasty were included, and circadian characteristics of natriuresis as well as heart rate variability indices, including 24‐hour BP, low‐frequency and high‐frequency (HF) components, and the percentage of differences between adjacent normal R‐R intervals >50 ms were evaluated using an oscillometric device, TM‐2425, both at baseline and 3 days after angioplasty. In both the fibromuscular dysplasia and atherosclerotic stenosis groups, 24‐hour systolic BP (fibromuscular dysplasia, −19±14; atherosclerotic renal artery stenosis, −11±9 mm Hg), percentage of differences between adjacent normal R‐R intervals >50 ms, HF, brain natriuretic peptide, and nighttime urinary sodium excretion decreased (all P<0.01), and heart rate increased (both P<0.05) after angioplasty. In both groups, revascularization increased the night/day ratios of percentage of differences between adjacent normal R‐R intervals >50 ms (both P<0.01) and HF, and decreased those of low frequency/HF (all P<0.05) and nighttime urinary sodium excretion (fibromuscular dysplasia, 1.17±0.15 to 0.78±0.09; atherosclerotic renal artery stenosis, 1.37±0.10 to 0.99±0.06, both P<0.01). Multiple logistic regression analysis indicated that a 1‐SD increase in baseline low frequency/HF was associated with at least a 15% decrease in 24‐hour systolic BP after angioplasty (odds ratio, 2.30 [95% CI, 1.03–5.67]; P<0.05). Conclusions Successful revascularization results in a significant BP decrease in the early postoperative period. Intrarenal perfusion might be a key modulator of the circadian patterns of autonomic nerve activity and natriuresis, and pretreatment heart rate variability evaluation seems to be important for treatment success.